Transmembrane Peptides as a New Strategy to Inhibit Neuraminidase-1 Activation - Albrecht, Camille; Kuznetsov, Andrey S.; Appert-Collin, Aline; Dhaideh, Zineb; Callewaert, Maïté; Bershatsky, Yaroslav V.; Urban, Anatoly S.; Bocharov, Eduard V.; Bagnard, Dominique; Baud, Stéphanie; Blaise, Sébastien; Romier-Crouzet, Béatrice; et al. (Frontiers in Cell and Developmental Biology, 2020)
Sialidases, or neuraminidases, are involved in several human disorders such as neurodegenerative, infectious and cardiovascular diseases, and cancers. Accumulative data have shown that inhibition of neuraminidases, such as NEU1 sialidase, may be a promising pharmacological target, and selective inhibitors of NEU1 are therefore needed to better understand the biological functions of this sialidase. In the present study, we designed interfering peptides (IntPep) that target a transmembrane dimerization interface previously identified in human NEU1 that controls its membrane dimerization and sialidase activity. Two complementary strategies were used to deliver the IntPep into cells, either flanked to a TAT sequence or non-tagged for solubilization in detergent micelles. Combined with molecular dynamics simulations and heteronuclear NMR studies in membrane-mimicking environments, our results show that these IntPep are able to interact with the dimerization interface of human NEU1, to disrupt membrane NEU1 dimerization and to strongly decrease its sialidase activity at the plasma membrane. In conclusion, we report here new selective inhibitors of human NEU1 of strong interest to elucidate the biological functions of this sialidase.